Actividad física deportiva y bienestar psicológico en estudiantes de la carrera profesional de Educación Física Facultad de Educación UNAP 2021 - Servan Rojas, Dutuledd (2025)
The research established as its main purpose to analyze the connection between sports physical activity practice and psychological well-being in students from the Physical Education academic program belonging to the Faculty of Education during 2021. The methodology employed corresponded to an applied descriptive approach, using a cross-sectional correlational design. The population universe consisted of 98 students, working with the entire population as the sample. For data collection, two instruments were implemented: a survey-type questionnaire designed to measure the Sports Physical Activity variable and a Likert Scale to evaluate the Psychological Well-being variable. The main findings revealed that, in the analysis of the association between sports physical activity and psychological well-being conducted with 98 students, a Pearson correlation coefficient rxy= 0.603 was identified, which evidences a high magnitude positive direct association. Consequently, the research determines that there exists a significant relationship between sports physical activity practice and psychological well-being in physical education students.